Class, migrant background and misrecognition of capital in the university admission - Kosunen Sonja; Niemi Anna-Maija; Laaksonen Linda Maria (Routledge, Taylor & Francis Group, 2022)
In this article, we discuss how class and migrant background intersect when students discuss their studies in general upper secondary education and their aspirations in university admission. We focus on the discussed social inequalities in student admission to one of the elite fields, medicine, in eight ethnographic interviews with students and fieldnotes concerning observations in two general upper secondary schools during an academic year. Admission to university-level medical education locally in Finland was constructed ‘impossible for me’ due to its high competitiveness. The symbolic violence in the self-perception and the misrecognition of capital in relation to interviewees’ multilingual background did not function as mobilisable capital in the national admission process. Admission becomes a platform for misrecognition of cultural and economic capital and for educational exclusion of working-class young people from migrant backgrounds from the medical profession. This happens on the surface in public and private education and health care even in a tuition-fee-free education system.